2007
DOI: 10.1186/1546-0096-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of joint cartilage thickness in large and small joints in healthy children: a clinical pilot study assessing observer variability

Abstract: Background: Loss of joint cartilage is a feature of destructive disease in JIA. The cartilage of most joints can be visualized with ultrasonography (US). Our present study focuses on discriminant validity of US in children. We studied reproducibility between and within a skilled and a non-skilled investigator of US assessment of cartilage thickness in small and large joints in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 12 publications
2
31
0
3
Order By: Relevance
“…Ossification of the secondary center was variable, depending on the bones of the joint evaluated, but overall it was usually not visible in the toddlers and infants, particularly in the hand joints. Since sex variation was not evaluated in the present study, no assumption can be drawn about sex or comparison made with other observations (14). The combination of B-mode with Doppler images has proven that synovial recesses of the 4 joints explored do not show any Doppler signal under normal circumstances.…”
Section: Discussionmentioning
confidence: 72%
“…Ossification of the secondary center was variable, depending on the bones of the joint evaluated, but overall it was usually not visible in the toddlers and infants, particularly in the hand joints. Since sex variation was not evaluated in the present study, no assumption can be drawn about sex or comparison made with other observations (14). The combination of B-mode with Doppler images has proven that synovial recesses of the 4 joints explored do not show any Doppler signal under normal circumstances.…”
Section: Discussionmentioning
confidence: 72%
“…32,33 In our study, cartilage was graded and the distal femoral cartilage thickness of the symptomatic knee was measured in females with knee OA using US, and we found that HQ-angle measurements were correlated with cartilage grading/thickness by US.…”
mentioning
confidence: 99%
“…They established the normal ranges of US-detected cartilage thickness in small and large joints by examining a cohort of 394 healthy children. Further, they demonstrated that cartilage was significantly thicker in boys than in girls and that cartilage thickness diminished progressively with age in both sexes 9,10 . Similar variations by sex and age were also found by Panghaal, et al, who used a different approach in the measurement of cartilage thickness in the knees of healthy subjects from birth to 21 years 11 .…”
Section: Ultrasound Measurement Of Cartilage Thickness In Childhood Amentioning
confidence: 99%